2022
DOI: 10.3389/fneur.2022.818395
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-Resident Macrophages in the Stria Vascularis

Abstract: Tissue-resident macrophages play an important role in clearance, development, and regulation of metabolism. They also function as sentinel immune cells, initiating inflammatory responses, clearing inflammatory debris, and maintaining homeostatic tissue environment. In the cochlea, the roles of tissue-resident macrophages include maintaining steady-state tissues, immunological defense, and repairing pathological conditions associated with noise, ototoxic drugs, aging, and various pathogens. Perivascular macroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Several previous studies in rodents have shown macrophage infiltration into the stria vascularis and the subsequent development of these macrophages into PVMs ( 36 , 42 ). Observations in the present study also demonstrated that PVMs in the stria vascularis originate from infiltrating macrophages ( Figure 5 ).…”
Section: Discussionmentioning
confidence: 91%
“…Several previous studies in rodents have shown macrophage infiltration into the stria vascularis and the subsequent development of these macrophages into PVMs ( 36 , 42 ). Observations in the present study also demonstrated that PVMs in the stria vascularis originate from infiltrating macrophages ( Figure 5 ).…”
Section: Discussionmentioning
confidence: 91%
“…Cochlear macrophages play an important role in homeostasis and during cochlear injury. PVMs are closely associated with the blood vessels and play a pivotal role in regulating the tight junction proteins between endothelial cells that comprise the BLB ( 34, 35 ). In noise damage models that result in the loss of hair cell synaptic ribbons, macrophages are involved in synaptic repair and the restoration of cochlear synapses and synaptic function ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages are one of the key elements of the intrinsic immune system in mature organs, and they primarily function as an immunological defense to keep the internal environment at homeostasis (Wynn and Vannella, 2016;Duan, 2018), and macrophages are resident immune cells in the cochlea (Liu et al, 2018;He et al, 2020). They play a continuous monitoring role in the homeostatic environment, thus helping maintain tissue homeostasis under pathological and physiological conditions (Ito et al, 2022). Cochlear resident macrophages exhibit remarkable plasticity, allowing them to rapidly switch between active phenotypes and adapt to changing neuronal and environmental conditions.…”
Section: Discussionmentioning
confidence: 99%